2018
DOI: 10.1021/acs.jpca.7b11356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Giant Ferromagnetic π–d Interaction in Iron-Phthalocyanine Molecule

Abstract: The interaction between itinerant π and localized d electrons in metal-phthalocyanines, namely, J interaction, is considered as responsible for the giant negative magnetoresistance observed in several phthalocyanine-based conductors, among many other important physical properties. Despite the fundamental and technological importance of this on-site intramolecular interaction, its giant ferromagnetic nature has been only recently demonstrated by the experiments conducted by Murakawa et al. in the neutral radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
2
5
0
Order By: Relevance
“…In Cl-(MnPc) 2 the moment stays at 3.74 μ B on Mn1, and it is lowered to −0.11 in the ring. The antiferromagnetic coupling observed in all these cases between the central metal and the organic ring was also been observed for several metal Pc’s deposited on surfaces, , while for some Pc-based 3D materials, it was found to be ferromagnetic, for example, in FePc (CN) 2 ·2CHCl 3 crystals …”
Section: Resultssupporting
confidence: 59%
“…In Cl-(MnPc) 2 the moment stays at 3.74 μ B on Mn1, and it is lowered to −0.11 in the ring. The antiferromagnetic coupling observed in all these cases between the central metal and the organic ring was also been observed for several metal Pc’s deposited on surfaces, , while for some Pc-based 3D materials, it was found to be ferromagnetic, for example, in FePc (CN) 2 ·2CHCl 3 crystals …”
Section: Resultssupporting
confidence: 59%
“…The effect of altering the structure of coumarins on its dye sensitizer properties has been studied by number of researchers. [70][71][72][73][74][75] Sanchez et.al. [70] have carried out exhaustive study about the effect of the substitutions, involving multiple substitution positions, on the absorbance behaviour and energy levels of the coumarins.…”
Section: Introductionmentioning
confidence: 99%
“…[70][71][72][73][74][75] Sanchez et.al. [70] have carried out exhaustive study about the effect of the substitutions, involving multiple substitution positions, on the absorbance behaviour and energy levels of the coumarins. The present work involves substitution at single position however, it gives a detailed account of such substitution on the dye -I 2 interaction and hence, back electron recombinations along with other optical as well as photovoltaic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical studies have served as a tool for verifying the results found experimentally. As such, number of such studies has been carried out, such as those based on coumarins [10][11][12][13][14][15][16] and triphenylamine. [17][18][19][20] Theoretical studies by several researchers [15,[21][22][23][24][25] on NKX coumarin derivatives have been carried for understanding the relationship between the molecular properties of these dye sensitizers and the energy conversion efficiency of DSSCs.Theoretical calculation, particularly DFT methods have evolved as very effective and useful tools for optimizing a system for achieving better results for efficient DSSCs.…”
mentioning
confidence: 99%
“…Researchers have worked on the different type of coumarins usually NKX-based ones, as donors for DSSC applications. [10][11][12][13][14][15][16] But, the basic coumarin molecules like bicoumarin, coumarin, dihydrofurano coumarin, furano coumarin, phenyl coumarin, pyranoanglar coumarin, and pyranolinear coumarin, have been hardly studied in this perspective. [49][50][51] In this regard, we have made an attempt to use these coumarin molecules as donors for the push-pull systems.…”
mentioning
confidence: 99%